Magnetic hysteresis properties in dilute ising ultra-thin-film: Monte Carlo investigation - Y. Laosiritaworn (2018)
Monte Carlo simulation was used to observe the dynamic magnetic behavior of dilute Ising ultra-thin-film. The hysteresis properties were investigated as varying the non-magnetic concentration, field frequency and field amplitude where the Metropolis algorithm was used. From the results, at fixed temperature and field amplitude, the hysteresis loop increases in size with increasing frequency at low frequency region but reduces at high frequency region due to the increase of the phase-lag between magnetization and external field signals. With the inclusion of non-magnetic sites, the phase-lag shifts to higher frequency as a result of weaker magnetic interaction. In addition, the scaling relation among the hysteresis area, the field parameters and non-magnetic concentration was proposed to provide general information of how the dilution affects hysteresis properties of dilute magnetic in ultra-thin-film structure. © 2008 Trans Tech Publications, Switzerland.